Analisis Deskriptif Brand Switching dan Purchase Intention Dampak Pemboikotan Merek Terkait dengan Peristiwa di Gaza - Sabilla Saberina (LPPM Universitas Informatika dan Bisnis Indonesia, 2024)
The background to the research was increased consumer concern for political and social issues, including support for a boycott of certain brands. The purpose of this study is to analyze the relationship between brand switching, purchase intent, and brand boycott related to the war in Gaza. The quantitative approach used in further research is also used in the genetic approach in this research using survey methods. The data is then collected and organized based on the observed experience of Israeli-related brands. Descriptive analysis is carried out to identify patterns of consumer behavior. The findings show that there is a tendency for consumers to switch to alternative brands that are not affiliated with Israel. Moreover, consumer purchasing intentions towards brands affiliated to Israel have decreased significantly. Implications of this study are the importance of understanding consumer behaviour in the context of political and social issues. The study also shows the potential impact of a boycott on certain brands. The study's main contribution was to provide insights into the relationship between Brand Switching, Purchase Intention, and boycott related political issues, as well as their implications for Israeli-affiliated brands.